Oak somatic and gametic embryos maturation is affected by charcoal and specific aminoacids mixture - Pintos, Beatriz; Manzanera, Jose a; Bueno, M. Angeles (Annals of Forest Science, 2010)
• Development of both somatic and gametic embryogenesis has many applications in clonal forestry and genetic improvement, for instance as mass-propagation of genetically improved plants and production of pure lines through doubled-haploid plant regeneration from gametic embryos. • The goal of this work was to improve growth, maturation and plantlet regeneration of cork oak (Quercus suber L.) embryos from both somatic and gametic origin. • Activated charcoal promoted a signiﬁcant increase in growth in terms of relative size and weight of both somatic and doubled-haploid embryos, as well as a more eﬃcient control of secondary somatic embryogenesis during development. A signiﬁcant interaction was also observed with amino acid nutrition. While some amino acids (i.e., glutamine, arginine or asparagine) did not show signiﬁcant diﬀerences with the controls, a mixture of these three amino acids or gamma amino butyric acid stimulated embryo growth. The highest survival rate during acclimation of plantlets from both somatic and doubled-haploid origin was obtained when the embryos had been previously cultured on basal medium with 3% sucrose and 1% activated charcoal for two months at 4 ◦ C and germinated on medium supplemented with 6-benzylaminopurine and indole-3-butyric acid. • We obtained more than 900 cork oak plantlets acclimated from several embryogenic lines, with a high survival rate, demonstrating that this methodology is applicable for large scale plantlet production. We also report the ﬁrst regeneration of doubled-haploid plantlets in cork oak.
Keywords: activated charcoal; amino acids; Cork oak; gametic embryo; plantlet acclimation